- ACCOUNTABILITY AND TRANSPARENCY IN UPDATING THE INTEGRATED SOCIAL WELFARE DATA FOR THE DISTRIBUTION OF THE FAMILY HOPE PROGRAM IN PESANGGRAHAN VILLAGE, CILACAP REGENCY: - - Oktinus Nafsilfi; Raden Imam Al Hafis (Indonesian Journal of Social Sciences, Policy and Politics, 2026)
The success of the Family Hope Program (PKH) is highly dependent on the accuracy of the Integrated Social Welfare Data (DTKS). However, DTKS updates at the village level still face obstacles that cause the target recipients of assistance to often be missed. This study aims to examine the transparency and accountability of DTKS updates and PKH distribution in Pesanggrahan Village (Kesugihan Subdistrict, Cilacap Regency). Using a descriptive qualitative approach, data were collected through in-depth interviews, observations, and document reviews involving 15 informants selected purposively. Findings indicate that transparency remains weak: public access to information is limited, complaint mechanisms are not functioning effectively, and community participation in village deliberations is minimal. Regarding accountability, discrepancies were found between DTKS data and on-the-ground realities, leading to inclusion errors (7.9%) and exclusion errors (7.9%). Key challenges include limited human resources, inadequate information technology infrastructure, and insufficient outreach. This study contributes to the literature by simultaneously examining transparency and accountability mechanisms at the village level, a perspective still underrepresented in prior research. Previous studies have largely focused on macro-level evaluations of PKH implementation, while limited attention has been paid to village-level governance mechanisms in updating welfare databases. Recommendations include strengthening community-based information systems, enhancing the capacity of village officials, and optimizing village deliberations as a platform for participatory social verification. The findings demonstrate that procedural accountability does not necessarily guarantee substantive targeting accuracy in decentralized welfare governance.